Clonal Hematopoiesis Is Associated With Low CD4 Nadir and Increased Residual HIV Transcriptional Activity in Virally Suppressed Individuals With HIV. (21st August 2021) - van der Heijden, Wouter A; van Deuren, Rosanne C; van de Wijer, Lisa; van den Munckhof, Inge C L; Steehouwer, Marloes; Riksen, Niels P; Netea, Mihai G; de Mast, Quirijn; Vandekerckhove, Linos; de Voer, Richarda M; van der Ven, Andre J; Hoischen, Alexander
Abstract: Clonal hematopoiesis, a common age-related phenomenon marked by expansion of cells with clonal hematopoiesis driver mutations, has been associated with all-cause mortality, cancer, and cardiovascular disease. People with HIV (PWH) are at risk for non-AIDS–related comorbidities such as atherosclerotic cardiovascular disease and cancer. In a cross-sectional cohort study, we compared clonal hematopoiesis prevalence in PWH on stable antiretroviral therapy with prevalence in a cohort of overweight individuals and a cohort of age- and sex-matched population controls. The prevalence of clonal hematopoiesis adjusted for age was increased and clone size was larger in PWH compared to population controls. Clonal hematopoiesis is associated with low CD4 nadir, increased residual HIV-1 transcriptional activity, and coagulation factors in PWH. Future studies on the effect of clonal hematopoiesis on the HIV reservoir and non-AIDS–related comorbidities are warranted. Abstract : The prevalence of clonal hematopoiesis mutations adjusted for age was increased and clone size was larger in people with HIV compared to uninfected controls. These mutations were associated with low CD4 nadir, increased residual HIV-1 transcriptional activity, and coagulation factors.